SISTEM INFORMASI INDEKS KEPUASAN MASYARAKAT TERHADAP PELAYANAN PUBLIK PADA DESA KARANG TENGAH KABUPATEN TANGGERANG BERBASIS WEB - Andika Rosi Wirayuda (2022)
Public service is a business carried out by public service institutions. To measure the level of community satisfaction with the services provided, a survey on the Community Satisfaction Index is needed. Karang Tengah Village is a public service institution that focuses on providing services to the community. However, until now, Karang Tengah Village does not yet have a system regarding the Community Satisfaction Index. Based on this, the authors designed and built a web-based Community Satisfaction Index Information System to facilitate the agency to determine community satisfaction with the services that have been provided. The method used by the author is the Waterfall Method with the PIECES analysis method, then the system design uses UML and is built using the native PHP programming language using the My SQL database and ends with a trial using the Black Box Testing Method. The creation of this website-based application makes Karang Tengah Village able to find out the Community Satisfaction Index for the services that have been provided and can evaluate the service performance of the village staff on duty.